2023
DOI: 10.3390/pharmaceutics15041225
|View full text |Cite
|
Sign up to set email alerts
|

Chrysin Is Immunomodulatory and Anti-Inflammatory against Complete Freund’s Adjuvant-Induced Arthritis in a Pre-Clinical Rodent Model

Abstract: Chrysin (5,7-dihydroxyflavone) has many pharmacological properties including anti-inflammatory actions. The objective of this study was to evaluate the anti-arthritic activity of chrysin and to compare its effect with the non-steroidal anti-inflammatory agent, piroxicam, against complete Freund’s adjuvant (CFA)-induced arthritis in a pre-clinical model in rats. Rheumatoid arthritis was induced by injecting CFA intra-dermally in the sub-plantar region of the left hind paw of rats. Chrysin (50 and 100 mg/kg) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…Arthritis is characterized by the infiltration of inflammatory cells, subcutaneous inflammation, and synovial inflammation ( Vishnu and Krishnan, 2018 ). These findings were consistent with the outcomes reported in studies involving the treatment of rats with complete Freund’s adjuvant-induced arthritis using chrysin ( Faheem et al, 2023 ).…”
Section: Discussionsupporting
confidence: 90%
“…Arthritis is characterized by the infiltration of inflammatory cells, subcutaneous inflammation, and synovial inflammation ( Vishnu and Krishnan, 2018 ). These findings were consistent with the outcomes reported in studies involving the treatment of rats with complete Freund’s adjuvant-induced arthritis using chrysin ( Faheem et al, 2023 ).…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with Kucukler et al (2) who demonstrated that lead acetate cause marked expression of TNF-α in renal glomeruli and interstitial tissue. This may be explained by oxidative stress, which stimulates Nuclear Factor Kappa B (NF-kB) and an inflammatory mechanism is triggered, which results in liberation of pro-inflammatory cytokines, mainly TNF-α (34) .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive evidence supports the notion that chrysin exerts a wide array of anti-inflammatory effects by targeting multiple molecular pathways and their associated targets ( Zeinali et al, 2017 ). Specifically, chrysin possesses anti-inflammatory effects by reducing the production of pro-inflammatory cytokines TNF, IL-1, and IL-6 ( Ahad et al, 2014 ; Faheem et al, 2023 ). However, the therapeutic effectiveness of chrysin has been hindered by its inadequate aqueous solubility and low bioavailability ( Li Y et al, 2019 ; Bhowmik et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%